Analisis Kepemimpinan Pendidikan; Kompetensi Kepala Sekolah - Rahmawati; Adinda Setiawati; Taufik Muhtarom (Journal Innovation In Education, 2024)
This research aims to find out the Analysis of Character Education Approaches in Various Countries. Character education is the main focus in various countries to build a young generation with morals and noble character. This research uses qualitative methods with data collection and analysis techniques by searching for literature through several books and scientific articles as well as other trusted sources. This article analyzes character education approaches in several countries, namely, Malaysia, Singapore and Japan. Each country has a different approach in instilling character values ​​in students. Indonesia uses the approach of instilling values, clarifying values, learning to do, leading by example and habituation. Singapore uses a curriculum-based, co-curricular and extracurricular approach, with a focus on leadership development, entrepreneurship and community service. Japan uses a culture and tradition-based approach, with an emphasis on values ​​such as discipline, respect, and responsibility. Analysis shows that there is no single most effective approach to character education. Each country must adapt its approach to its own cultural and social context.